A Comparative Study of Australian and New Zealand Male and Female Nurses' Health: A Sex Comparison and Gender Analysis. (November 2016) - Tuckett, Anthony; Henwood, Tim; Oliffe, John L.; Kolbe-Alexander, Tracy L.; Kim, Jae Rin
The aim of this research was to compare the health and lifestyle behaviors between male and female nursing professionals. Biological, workplace, and lifestyle factors as well as health behaviors and outcomes are reported as different between male and female nurses. Although male nurses show distinct health-related patterns and experience health disparities at work, few studies have investigated health differences by sex in a large cohort group of nursing professionals. This observation study of Australian and New Zealand nurses and midwives drew data from an eCohort survey. A cohort of 342 females was generated by SPSS randomization (total N=3625), to compare against 342 participating males. Measures for comparison include health markers and behaviors, cognitive well-being, workplace and leisure-time vitality, and functional capacity. Findings suggest that male nurses had a higher BMI, sat for longer, slept for less time, and were more likely to be a smoker than their female nurse counterparts. Men were more likely to report restrictions in bending, bathing, and dressing. In relation to disease, male nurses reported greater rates of respiratory disease and cardiovascular disease, including a three times greater incidence of myocardial infarction, and were more likely to have metabolic problems. In contrast, however, male nurses were more likely to report feeling calm and peaceful with less worries about their health. Important for nurse workforce administrators concerned about the well-being of their staff, the current study reveals significant sex differences and supports the need for gender-sensitive approaches to aid the well-being of male nurses.